Utilizing Online Platforms In Teaching and Learning English In the Preparatory Year Program at IAU - Alfehaid, Abdulaziz Fahad Turki (جامعة الحسين بن طلال - عمادة البحث العلمي والدراسات العليا, 2017)
The purpose of this paper is to present a study on the utility of online e-learning platforms for teaching and learning English in the Preparatory Year Program in Imam Abdurrehman bin Faisal University, Dammam, Saudi Arabia. To investigate the utilization of online e-learning platforms, the researcher mainly used questionnaires. The participants of the study were 74 English language teachers and 1533 students of the PYP. The findings of the study imply that online e-learning platforms help teachers interact with their students. The study also suggests that the online written feedback tool is helpful in improving students’ writing skills. The study also implies that the more students use online platforms, the better they are engaged in language learning. The study also suggests that teachers’ in-class teaching practices are further supported by utilizing the online activities and continuous assessment tools. The study concludes that there should be a fully operational online support system and information communications technical team in order to facilitate the online learning and teaching English in PYP.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- اللغة الإنجليزية -- السنة التحضيرية -- المنصات التعليمية -- وسائل الإتصالات -- تكنولوجيا المعلومات -- شبكة الإنترنت -- مستخلصات الأبحاث -- الترجمة -- اللغات الأجنبية